Prevalence and Determinants of Hypertension in Indonesia - Eny Dwimawati; Fitri Dian Nila Sari; Evamona Sinuraya; Purwaningsih (Indian Journal of Forensic Medicine & Toxicology, 2021)
It is estimated that there are 15 million people with Hypertension in Indonesia, but only 4% are controlled.The prevalence of hypertension sufferers is relatively high, 7% to 22%. Prevention of Hypertension can bedone by eliminating or minimizing risk factors, one of which causes it, such as reducing salt consumption,if not done, then there is a risk of Hypertension. This study aims to determine the risk factors with thebehaviour of Hypertension in Puskesmas. This research is a quantitative study with a cross-sectional method.A sample of 225 respondents who visited/sought treatment at the health centre using Accidental Samplingtechnique. Data analysis was performed using the chi-square test. The results showed that the factorscausing Hypertension were age, exercise habits, smoking habits, alcohol consumption, nutritional status,sodium intake and stress. To reduce people suffering from Hypertension, the Puskesmas should be able toprovide information to the public about Hypertension and how to prevent it by doing health promotion orcounselling either individually or in groups.